Peningkatan Kemampuan Problem Solving Mahasiswa Sebagai Calon Guru Fisika Menggunakan Socratic Dialogue - Nurita Apridiana Lestari (Momentum: Physics Education Journal, 2017)
Mastery of the concepts of physics students can be measured by its ability to solve the problems of physics. Problem solving ability is one component that must be owned by the students as a physics teacher candidates. Based on the results of initial observations, it is known that the problem solving ability of students is still low, especially associated with the use of physics concepts to solve problems. Therefore, the ability of problem solving should be trained in teaching as a form of scaffolding for students. Scaffolding can be done through the method of Socratic dialogue which is the provision of structured questions to help students find answers to the problems of physics using the right concept. This type of research is the Classroom Action ResearchÃ‚Â  with two cycles were performed on physics student teachers in the subjects Physics 1 with a fluid material. Improved problem solving ability was measured using test items at the end of the cycle. The results qualitatively show their developments and increased activity in the classroom compared to learning before the action. These results are supported quantitatively by an increase in average test scores of the first cycle of 70.00 into 75.86 in the second cycle.Ã‚Â Keywords: problem solving, socratic dialogueÃ‚Â Penguasaan konsep fisika mahasiswa dapat diukur dari kemampuannya dalam memecahkan permasalahan fisika (problem solving). Kemampuan problem solving merupakan salah satu komponen yang harus dimiliki oleh mahasiswa sebagai calon guru fisika. Berdasarkan hasil observasi awal, diketahui bahwa kemampuan problem solving mahasiswa masih rendah, khususnya terkait dengan penggunaan konsep fisika untuk memecahkan masalah. Oleh karena itu, kemampuan problem solving perlu dilatihkan dalam pembelajaran sebagai bentuk scaffolding bagi mahasiswa. Scaffolding dapat dilakukan melalui metode socratic dialogue yang merupakan pemberian pertanyaan terstruktur untuk membantu mahasiswa menemukan jawaban permasalahan fisika menggunakan konsep yang tepat. Jenis penelitian ini adalah Penelitian Tindakan Kelas (PTK) dengan 2 siklus yang dilakukan pada mahasiswa calon guru fisika pada matakuliah Fisika Dasar 1 dengan materi Fluida. Peningkatan kemampuan problem solving diukur menggunakan butir soal tes di akhir siklus. Hasil penelitian secara kualitatif menunjukkan adanya perkembangan dan peningkatan aktivitas di kelas dibandingkan dengan pembelajaran sebelum adanya tindakan. Hasil tersebut didukung secara kuantitatif melalui peningkatan rata-rata nilai tes dari siklus I sebesar 70,00 menjadi 75,86 pada siklus II.Ã‚Â Kata Kunci: problem solving, socratic dialogueÃ‚Â